Addenbrooke's cognitive examination III: diagnostic utility for detecting mild cognitive impairment and dementia in Parkinson's disease - Sousa, Nariana Mattos Figueiredo; Brucki, Sonia Maria Dozzi (Arquivos de Neuro-Psiquiatria, 2023)
Background Cognitive deficit in Parkinson disease (PD) is an important cause of functional disability in these patients and early detection, with sensitive instruments, can contribute to longitudinal monitoring.Objective To investigate the diagnostic accuracy, sensitivity, and specificity of the Addenbrooke's Cognitive Examination-III in patients with PD, using the comprehensive neuropsychological battery as reference method.Methods Cross-sectional, observational, case-control study. Setting: rehabilitation service. A total of 150 patients and 60 healthy controls matched for age, sex, and education. For level I assessment, Addenbrooke Cognitive Examination (ACE-III) was used. Level II assessment used a comprehensive neuropsychological battery of standardized tests for this population. All patients remained in on-state during the study. The diagnostic accuracy of the battery was investigated through the receiver operating characteristic (ROC) analysis.Results The clinical group was divided into 3 subgroups: normal cognition in Parkinson's disease (NC-PD-16%), mild cognitive impairment due to Parkinson's disease (MCI-PD-69.33%), and dementia due to Parkinson's disease (D-PD-14.66%). ACE-III optimal cutoff scores for detecting MCI-PD and D-PD were 85/100 (sensitivity 58.65%, specificity 60%) and 81/100 points (sensitivity 77.27%, specificity 78.33%), respectively. Age was inversely associated with the performance of the scores (totals and domains of the ACE-III), while the level of education had a significantly positive correlation in the performance of these scores.Conclusions ACE-III is a useful battery for assessing the cognitive domains and to differentiate individuals with MCI-PD and D-PD from healthy controls. Future research, in a community setting, is necessary to provide discriminatory capacity of ACE-III in the different severities of dementia.
Keywords: Parkinson Disease; Cognitive Dysfunction; Dementia; Neuropsychological Tests